IMPLEMENTASI AKAD MURABAHAH BIL WAKALAH PADA PRODUK PEMBIAYAAN (Penelitian di Koperasi Simpan Pinjam dan Pembiayaan Syariah Al-Uswah Banjar) - Repa Nur Elisa; Ahmad Agung (Fakultas Ekonomi dan Bisnis Islam, Institut Agama Islam Darussalam (IAID) Ciamis, Jawa Barat, INDONESIA, 2019)
This study aims to determine (1) the mechanism for using murabahah bi wakalah contracts for KSPPS members; (2) benefits of murabahah bil wakalah financing contract for members of KSPPS Al-Uswah Banjar; (3) the implementation of the murabahah bil wakalah contract on the financing product of KSPPS Al-Uswah Banjar members. This qualitative research uses a case study method. Data collection techniques used direct observation to the KSPPS Al-Uswah office, conducting interviews with managers, employees and customers who carried out murabahah financing at KSPPS Al-Uswah, and relevant documentation. The results of the study illustrate that the mechanism of the murabahah bil wakalah financing contract in KSPPS the contract that is carried out first is the wakalah contract, the benefits of the murabahah bil wakalah financing contract for members are to provide an easy process in terms of financing and help SMEs that need business capital, and the implementation of the murabahah bil contract. wakalah at KSPPS Al-Uswah Banjar has not been in line with DSN MUI Fatwa No. 04/DSN-MUI/IV/2000 concerning murabahah in the first stipulation paragraph 9 states,